2015
DOI: 10.1111/1759-7714.12142
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for acute radiation pneumonitis in postoperative intensity modulated radiation therapy and volumetric modulated arc therapy of esophageal cancer

Abstract: BackgroundRadiation pneumonitis (RP) is a common side reaction in radiotherapy for esophageal cancer. There are few reports about RP in esophageal cancer patients receiving postoperative intensity modulated radiation therapy (IMRT) and volumetric modulated arc therapy (VMAT). This study aims to analyze clinical or dosimetric factors associated with RP, and provides data for radiotherapy planning.MethodsWe reviewed 68 postoperative esophageal cancer patients who were treated with radiotherapy at the West China … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 38 publications
2
14
0
1
Order By: Relevance
“…Patients with high lung V 30 (exceed 14.2%) suffered 2.92-fold increased risk of RP compared to those with low V 30 (no more than 14.2%). Other two studies also considered lung V 30 as an independent predictor for the occurrence of symptomatic RP [19,21]. In our study, the SIB-VMAT plans achieved a sharp reduction in lung V 30 , with median decreased proportion of 8.7%, which would benefit a lot in the reduction of lung toxicities.…”
Section: Plan Comparisonsupporting
confidence: 49%
“…Patients with high lung V 30 (exceed 14.2%) suffered 2.92-fold increased risk of RP compared to those with low V 30 (no more than 14.2%). Other two studies also considered lung V 30 as an independent predictor for the occurrence of symptomatic RP [19,21]. In our study, the SIB-VMAT plans achieved a sharp reduction in lung V 30 , with median decreased proportion of 8.7%, which would benefit a lot in the reduction of lung toxicities.…”
Section: Plan Comparisonsupporting
confidence: 49%
“…It remains an attractive modality largely owing to the intimate anatomic relationship of the esophagus with both lungs and the heart. Indeed, several publications have posited a positive correlation between radiation dose to the lungs [ 14 18 ] and heart [ 19 22 ], with the risk of toxicities in these structures. Hence, the high conformality of IMRT could theoretically afford fewer toxicities to these organs-at-risk (OARs), especially in the setting of relative dose-escalation with dCRT, but supportive data are currently lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Another two studies also considered lung V 30 as an independent predictor for the occurrence of symptomatic RP. 24,26 In our study, the SIB-VMAT plans achieved a sharp reduction in lung V 30 , with median decreased proportion of 8.7%, which would benefit a lot in the reduction of lung toxicities. Xia et al 27 compared the SIB-IMRT with C-IMRT plans, and found that the SIB-IMRT plans got lower mean dose, V 5 and V 20 of total lung.…”
Section: Discussionmentioning
confidence: 53%